2010
DOI: 10.1007/s00441-010-0982-8
|View full text |Cite
|
Sign up to set email alerts
|

Hypoxia increases Sca-1/CD44 co-expression in murine mesenchymal stem cells and enhances their adipogenic differentiation potential

Abstract: Mesenchymal stem cells (MSCs) are usually cultured under normoxic conditions (21% oxygen). However, in vivo, the physiological "niches" for MSCs have a much lower oxygen tension. Because of their plasticity, stem cells are particularly sensitive to their environments, and oxygen tension is one developmentally important stimulus in stem cell biology and plays a role in the intricate balance between cellular proliferation and commitment towards differentiation. Therefore, we investigated here the effect of hypox… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
30
0
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 45 publications
(37 citation statements)
references
References 34 publications
6
30
0
1
Order By: Relevance
“…Oxygen tension within the marrow microenvironment is physiologically lower than other tissues and the diabetes status may further alter cellular homeostasis. Indeed, some authors have shown reduced differentiation of MSC toward either adipose or osteoblast phenotype [202, 203], while others suggested an increased differentiation of MSC under hypoxia conditions [204, 205]. Finally, hyperglycemia-induced acidosis may enhance bone resorption and impair bone quality [128].…”
Section: Diabetes-bone Interactionmentioning
confidence: 99%
“…Oxygen tension within the marrow microenvironment is physiologically lower than other tissues and the diabetes status may further alter cellular homeostasis. Indeed, some authors have shown reduced differentiation of MSC toward either adipose or osteoblast phenotype [202, 203], while others suggested an increased differentiation of MSC under hypoxia conditions [204, 205]. Finally, hyperglycemia-induced acidosis may enhance bone resorption and impair bone quality [128].…”
Section: Diabetes-bone Interactionmentioning
confidence: 99%
“…However, contrasting results have also been reported. Preexposure of adipose tissue-derived MSCs to hypoxia (2% O 2 ) increased their adipogenic potential [62,63], and 8% O 2 accelerated bone marrow-derived MSC differentiation [64]. Taken together, extremely low PO 2 seems to increase proliferation but no consensus has been reached at the moment regarding its effect on differentiation towards the adipogenic lineage.…”
Section: Proliferation and Adipogenic Differentiationmentioning
confidence: 96%
“…In 1895, Hammar posited that adipocytes arise from undifferentiated stem cells of a primitive mesenchymal type (Hammar, 1895). Since then, the ability of mesenchymal stem cells to differentiate into adipocytes in culture has been shown repeatedly (Kim et al, 2010;Lim et al, 2011;Qian et al, 2010;Scott et al, 2011;Styner et al, 2010;Valorani et al, 2010;Welter et al, 2013) because sets of mesenchymal markers can be used to enrich adipogenic precursors from the stromal vascular fraction Rodeheffer et al, 2008). This was further corroborated by the identification of Pref-1 ( preadipocyte factor 1) as a marker for early adipocyte precursor cells (Hudak et al, 2014).…”
Section: Mesenchymal Stem Cellsmentioning
confidence: 97%